Association of Worksite Wellness Center Attendance With Weight Loss and Health Care Cost Savings: Mayo Clinic's Experience. Issue 3 (March 2015) - Borah, Bijan J.; Egginton, Jason S.; Shah, Nilay D.; Wagie, Amy E.; Olsen, Kerry D.; Yao, Xiaoxi; Lopez-Jimenez, Francisco
Abstract : Objective: To assess the impact of wellness center attendance on weight loss and costs. Methods: A retrospective analysis was conducted using employee data, administrative claims, and electronic health records. A total of 3199 employees enrolled for 4 years (2007 to 2010) were included. Attendance was categorized as follows: 1 to 60, 61 to 180, 181 to 360, and more than 360 visits. Weight loss was defined as moving to a lower body mass index category. Total costs included paid amounts for both medical and pharmacy services. Results: Subjects with 181 to 360 and more than 360 visits were 46% ( P = 0.05) and 72% ( P = 0.01) more likely to have body mass index improvement compared with those with 1 to 60 visits. Compared with the mean annual cost of $13, 267 for 1 to 60 visits, the mean for subjects with 61 to 180, 181 to 360, and more than 360 visits had significantly lower costs at $9538, $9332 and $8293, respectively (all P < 0.01). Higher attendance was associated with weight loss and significantly lower annual costs.